How does the number of small goals affect national-level female soccer players in game-based situations? Effects on technical-tactical, physical, and physiological variables - Alaune, D.; Snieckus, A.; Travassos, B.; Chmura, P.; Pizarro, D.; Coutinho, D. (Sensors, 2025)
This study investigated the impact of varying the number of small goals on elite female soccer players` decision-making, technical-tactical skills, running performance, and perceived exertion during game-based situations (GBSs). Sixteen national female players (aged 22.33 ± 2.89 years) participated in three conditions within an 8vs8 game without a goalkeeper (45 × 40 m), each featuring a different number of small goals (1.2 × 0.8 m): (i) 1 small goal (1G); (ii) 2 small goals (2G); and (iii) 3 small goals (3G). Sensors to track players` positioning, perceived exertion, and notational analysis were used to evaluate player performance. The results indicated that players covered a greater distance at low intensity during the 2G condition compared to both 1G (p = 0.024) and 3G (p = 0.05). Conversely, the 3G condition promoted a higher distance covered at high intensity compared to 2G (p = 0.05). The 1G condition resulted in fewer accelerations (2G, p = 0.003; 3G, p < 0.001) and decelerations (2G, p = 0.012) compared to conditions with additional goals. However, there were no statistically significant effects on technical-tactical actions. Notably, a trend toward improved decision-making was observed in the 1G condition compared to 2G (ES = -0.64 [-1.39; 0.11]) and a longer ball possession duration compared to 3G (ES = -0.28 [-0.71; 0.16]). In conclusion, coaches working with elite female soccer players can strategically vary the number of goals to achieve specific physical aims (i.e., using 2G to emphasize acceleration and deceleration or 3G to promote high-intensity distance) with minimal effects on their perceived fatigue, technical-tactical variables, and decision-making.